2018
DOI: 10.1557/adv.2018.194
|View full text |Cite
|
Sign up to set email alerts
|

Freeze-cast Porous Chitosan Conduit for Peripheral Nerve Repair

Abstract: A novel freeze-cast porous chitosan conduit for peripheral nerve repair with highly-aligned, double layered porosity, which provides the ideal mechanical and chemical properties was designed, manufactured, and assessed in vivo. Efficacies of the conduit and the control inverted nerve autograft were evaluated in bridging 10-mm Lewis rat sciatic nerve gap at 12 weeks post-implantation. Biocompatibility and regenerative efficacy of the porous chitosan conduit were evaluated through the histomorphometric analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 9 publications
(10 reference statements)
2
40
1
1
Order By: Relevance
“…The pores closer to the inner and outer stent surfaces were more spherical than lamellar and had shorter pore axes, s < 25 μm; they were also smaller in size and more precisely radially aligned than those in the stent wall center, where the structure was more lamellar and the shorter pore axes ranged from 40-60 μm. In contrast to our earlier findings for conduits made by freeze-casting the same chitosan solution between a 4 mm inner diameter aluminum tube and 2 mm diameter copper rod [69], no distinct membrane that separates the stent wall into an inner and an outer layer was observed. The observed pore structure was preserved also in the fully hydrated state ( Figure 2B), however some swelling occurred with the diameter of the porous stents increasing from 2.51 ± 0.05 mm in the dry state to 2.99 ± 0.02 mm in the wet.…”
Section: Microstructurecontrasting
confidence: 99%
See 1 more Smart Citation
“…The pores closer to the inner and outer stent surfaces were more spherical than lamellar and had shorter pore axes, s < 25 μm; they were also smaller in size and more precisely radially aligned than those in the stent wall center, where the structure was more lamellar and the shorter pore axes ranged from 40-60 μm. In contrast to our earlier findings for conduits made by freeze-casting the same chitosan solution between a 4 mm inner diameter aluminum tube and 2 mm diameter copper rod [69], no distinct membrane that separates the stent wall into an inner and an outer layer was observed. The observed pore structure was preserved also in the fully hydrated state ( Figure 2B), however some swelling occurred with the diameter of the porous stents increasing from 2.51 ± 0.05 mm in the dry state to 2.99 ± 0.02 mm in the wet.…”
Section: Microstructurecontrasting
confidence: 99%
“…We focus in this study on the microstructure, mechanical properties, and flow characteristics of this newly developed, freeze-cast stent design. Porous chitosan stents were manufactured by freeze-casting using a bi-directional, radial thermal gradient ( Figure 1A) [69,70]. The stent microstructures were investigated both in the dry and fully hydrated states.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Yuan, Zhang, Yang, Wang, and Gu () have shown that chitosan fibers support the adhesion, migration, and proliferation of SCs that result in axonal regeneration in the PNS. Various studies have demonstrated that transplantation of chitosan‐based nerve conduits in 1‐cm gaps or more with or without cells in the rat nerve repair models can induce nerve regeneration and repair damaged nerve (Fregnan et al, ; Guo et al, ; Meyer et al, ; Ruini et al, ; Yin et al, ). A recent study has also reported that chitosan conduits filled with simvastatin/Pluronic F‐127 hydrogel promote peripheral nerve regeneration and motor functional recovery in rats with 10‐mm sciatic nerve defects (Guo et al, ).…”
Section: Materials For Fabricating Nerve Conduitsmentioning
confidence: 99%
“…Compression tests were performed parallel to the cylinder axis on dry samples of 5 mm length and 4 mm diameter at ambient conditions (22–24 °C and r.h. 52–55%) on an Instron 5498 (Instron, Norwood, MA) with a 50 N load cell at cross-head speed of 0.05 mm s −1 (strain rate of 0.01/s). Compression was chosen to mimic in vivo loading conditions [2] , [3] , [6] , [7] , [8] , [9] . The modulus (the slope of initial linear region), yield strength (yield point, if present, otherwise the intersection of the initial linear slope and the slope of the initially linear plateau region), and toughness (work to 60% strain) were determined from the stress-strain curves.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%